Discourse of Youth Nationalism in the ''Vuca” Era (Volatility, Uncertainty, Complecity, Ambiguity): An Cultural Analysis - Soelistyowati, Rr Dinar (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Currently we live in the era of VUCA (Volatility, Uncertainty, Complexity, Ambiguity) where social change is very fast and unpredictable. It is influenced by many factors that are difficult to control, truth and reality are very subjective. In the past, we were taught to love the nation and country by diligently following the flag ceremony at school and other rules that had been prepared by the teaching materials produced by the government. But now the millennial generation can show their loyalty by presenting artistic and cultural attractions that can take various forms. Psychologically the condition of today's young generation is very different from the previous younger generation. The previous younger generation was synonymous with obeying rules, ethics and other polite attitudes. While the current generation is more open, expressive & democratic. This research wants to see from the psychological aspect of communication how the current millennial generation responds to vuca in its obligations as a nation and a state.